Activated carbons from biomass-based sources for CO2 capture applications. (November 2021) - Abuelnoor, Nada; AlHajaj, Ahmed; Khaleel, Maryam; Vega, Lourdes F.; Abu-Zahra, Mohammad R.M.
Abstract: In an ever-growing attempt to reduce the excessive anthropogenic CO2 emissions, several CO2 capture technologies have been developed in recent years. Adsorption using solid carbonaceous materials is one of the many promising examples of these technologies. Carbon-based materials, notably activated carbons, are considered very attractive adsorbents for this purpose given their exceptional thermal stability and excellent adsorption capacities. More importantly, the ability to obtain activated carbons from agricultural wastes and other biomass that are readily available makes them good candidates for several industrial applications ranging from wastewater treatment to CO2 adsorption, among others. Activated carbons from biomass can be prepared using various techniques, resulting in a range of textual properties. They can also be functionalized by adding nitrogen-based groups to their structure that facilitates faster and more efficient CO2 capture. This review provides a detailed overview of the recent work reported in this field, highlighting the different preparation methods and their differences and effects on the textual properties such as pore size, surface area, and adsorption performance in terms of the CO2 adsorption capacity and isosteric heats. The prospect of activated carbon functionalization and its effect on CO2 capture performance is also included. Finally, the review covers some of the pilot-plant scale processes in which these materials have been tested. Some identified gaps in the field have been highlighted, leading to the perspectives for future work. Graphical abstract: Image 1 Highlights: A review on activated carbon from biomass-based sources for CO2 capture. An overview of the synthesis process through physical and chemical activation, and their effect on adsorbent properties. Recent development with respect to activation methods and the effect on CO2 adsorption capacity. Amine functionalization of activated carbon and its effect on CO2 adsorption. Pilot plant testing and challenges of commercialization.